Mitochondrial permeability transition in protozoan parasites: what we learned from Trypanosoma cruzi - Bustos, Patricia L. (2017)
Fil: Bustos, Patricia L. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Parasitología Dr. Mario Fatala Chaben; Argentina.